Margins and Metropolis : Authority Across the Byzantine Empire - Herrin, Judith (Princeton University Press, 2013)
Cover -- ALSO BY JUDITH HERRIN -- Title -- Copyright -- Dedication -- Contents -- Abbreviations -- Introduction -- MARGINS -- 1. A Christian Millennium: Greece in Byzantium-How the Empire Worked at Its Edge -- 2. Aspects of the Process of Hellenization in the Early Middle Ages -- 3. Realities of Provincial Government: Hellas and Peloponnesos,1180-1204 -- 4. The Ecclesiastical Organization of Central Greece at the Time of Michael Choniates: New Evidence from the Codex Atheniensis 1371 -- 5. The Collapse of the Byzantine Empire in the Twelfth Century: A Study of a Medieval Economy -- 6. Byzantine Kythera -- METROPOLIS -- 7. Byzantium: The Palace and the City -- 8. Philippikos and the Greens -- 9. Philippikos "the Gentle" -- 10. The Historical Context of Iconoclast Reform -- 11. Constantinople, Rome, and the Franks in the Seventh and Eighth Centuries -- 12. The Pentarchy: Theory and Reality in the Ninth Century -- 13. From Bread and Circuses to Soup and Salvation: The Origins of Byzantine Charity -- 14. Ideals of Charity, Realities of Welfare: The Philanthropic Activity of the Byzantine Church -- 15. Mathematical Mysteries in Byzantium: The Transmission of Fermat's Last Theorem -- 16. Book Burning as Purification in Early Byzantium -- Index.